Physical Parameter Identification of Time-Varying Structure Using Partial Measurements - Yang, Ning (Curtin University, 2021)
In this thesis, based on the wavelet multiresolution analysis and Kalman filter (KF) series algorithms, methods to identify the time-varying physical parameters are investigated for linear structures, large-scale linear structures and nonlinear structures by using partial measurements. It is further extended to the identification of gradually varying physical parameters based on discrete cosine transform and KF using partial measurements. In addition, a structural damage detection algorithm based on temporal moments is proposed by using only incomplete measured structural responses.